2012
DOI: 10.1371/journal.pone.0029275
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Generation of MicroRNA Sponges for MicroRNA Inhibition

Abstract: MicroRNA (miRNA) sponges are transcripts with repeated miRNA antisense sequences that can sequester miRNAs from endogenous targets. MiRNA sponges are valuable tools for miRNA loss-of-function studies both in vitro and in vivo. We developed a fast and flexible method to generate miRNA sponges and tested their efficiency in various assays. Using a single directional ligation reaction we generated sponges with 10 or more miRNA binding sites. Luciferase and AGO2-immuno precipitation (IP) assays confirmed effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 32 publications
2
111
0
1
Order By: Relevance
“…Luciferase reporter plasmids were transfected into HCT116 cells seeded in 12-well plates using Lipofectamine 2000 (Invitrogen) per the manufacturer's suggestions. MiR-215 sponge was constructed as described previously (34) and as shown in SI Appendix, Fig. S7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase reporter plasmids were transfected into HCT116 cells seeded in 12-well plates using Lipofectamine 2000 (Invitrogen) per the manufacturer's suggestions. MiR-215 sponge was constructed as described previously (34) and as shown in SI Appendix, Fig. S7.…”
Section: Methodsmentioning
confidence: 99%
“…S7 A and B). The sponge was created as described previously (34) and was validated on the basis of its ability to de-repress a synthetic miR-215 target reporter construct (SI Appendix, Fig. S7 C and D).…”
Section: Mir-215mentioning
confidence: 99%
“…Therefore, the absorption of such overexpressed miRNAs by synthetic circRNAs should be investigated for their potential as cancer suppressors. Studies describing a new sponge technology indicated that circRNAs can be ef-fective in de-repression of miRNA target genes in cellular systems [39]- [41]. In one such study, Kluiver and colleagues have developed a fast and efficient method to generate sponges that can be applied to inhibit one or more miRNAs.…”
Section: Health Relevance and Potential Uses In Biomedicinementioning
confidence: 99%
“…Using different vector to oligo duplex ratios, the number of the miRNA binding sites can be controlled. The authors used several different approaches to demonstrate that the sponges are efficient inhibitors of miRNAs [39]. They performed luciferase assays to confirm that miRNAs can bind to the sponges in a dose dependent manner.…”
Section: Health Relevance and Potential Uses In Biomedicinementioning
confidence: 99%
“…It has been shown that adeno-associated virus-delivered TuDs induced long-term miRNA inhibition in mice [27,28]. TuDs and sponges are both more effective when the miRNA binding sites are non-complementary to the target miRNA at position 10–11, presumably because Ago2-dependent cleavage of the TuD is prevented [23,25,29]. Whether TuD activity is mediated by miRNA sequestration alone, or also by miRNA degradation remains unclear, since several studies have reported conflicting results [20,23,27].…”
Section: Introductionmentioning
confidence: 99%